ELT MATERIAL FOR BIOLOGY EDUCATION DEPARTMENT STUDENTS: WHAT ARE THE STUDENTS' NEEDS? - Sitti Nurpahmi; Hasriani Hasriani (Univeristas Islam Negeri (UIN) Alauddin Makassar, 2021)
This research is aimed to analyze the need of Biology Education Department Students at UIN Alauddin Makassar. Based on the preliminary study, the researcher found that English subject on Biology Education does not have a specific syllabus and also the material is not through the need analysis based on priorities needed by students of Biology Education Department. The research design used in this study was survey method. This need analysis comprises of Target Situation Analysis, Present Situation Analysis, and Learning Needs. The procedures included analyzing need by spreading questionnaire and conduct an interview. The result of this research shows that students of Biology Education Department needs more specific English material and need English reading skills more than other skills. It implies that the lecturer should design material related to the students need to fulfill their needs.